KAJIAN NASKAH: KITAB SAIRU AL-SALIKIN LI BABI IHYA ’ULUMUDDIN KARYA SYEKH ALI IBN ABDURRAHMAN AL-KALANTANI - Syamruddin Nasution (Sosial Budaya, 2014)
This work is an attempt to present one of the famous works by classical Malay scholar, Syaykh ‘Alī ibn ‘Abd al-Ramān al-Kalantanī, entitled Sayr al-Sālikīn.Comprised of 4 volumes, the book itself was a commentary on Imām al-Ghazālī’s magnum opus, Iyā’ ‘Ulūm al-Dīn, and was written in classical Malay scripts. The description of the book presented in this work focuses only to the first ten chapters of the 3rd volume of the Sayr, which speaks about things related to the heart, the levels of soul (nafs) and the ways to purify them, the danger of carnal soul and tongue, the impact of anger, and the negative aspects of the worldly life